Voice onset time for stutterers and non-stutterers - Babul Basu (Journal of All India Institute of Speech and Hearing, 1970)
The notion that the larynx is a culprit for stuttering dates back as early as the eleventh century. Recently the explanation regarding the basic nature, cause and maintenance of stuttering has been given on the basis of laryngeal dysfunction. Voice Onset Time (VOT) is one of the parameters among the temporal aspect of speech, which indicates laryngeal funcl:ion. VOT has been defined as "The duration between the release of a complete articulatory constriction or burst transient and the onset of phonation" (Lisker and Abramson, 1964,1967). Studies have shown that VOT in stutterers is longer than that of non~stutterer in case of English stop sounds.